Arang Kulit Biji Kakao (Theobroma cacao L) sebagai Adsorben untuk Menurunkan Kadar Asam Lemak Bebas pada Pembuatan Biodiesel dari Minyak Jelantah - Prasetyo, Dafit Ari; Saputro, Muhammad Rio Aditya; Ulma, Zeni (Jurnal Teknik Terapan, 2023)
Indonesia as one of the largest producing and exporting countries of crude palm oil (CPO). However, Indonesia still has not utilized the potential of the waste that generated by using CPO as cooking oil, namely used cooking oil. The high content of free fatty acids (FFA) in used cooking oil will cause the saponification reaction and interfere the processing into biodiesel. Cocoa bean shell charcoal (Theobroma cacao L) has a K2CO3 content similar to its commercial product, and contains some traces of silicates and sulfates so that it can increase the efficiency of reducing free fatty acids. In this study, tests were carried out to reduce FFA levels in used cooking oil using charcoal from cocoa bean husks activated with HCl, varying the concentrations of 6, 8 and 10 Molar, as well as the temperature treatment during the process of mixing used cooking oil with activated charcoal adsorbent, which was 75 , 100, and 150°C. The best FFA reduction results were found in the A3T2 reactor which reached 80%, where the best HCl concentration was 10 Molar and the temperature of the mixing process with the adsorbent was 100°C and produced a biodiesel yield of 75%. The quality of the biodiesel produced complies with SNI 7182-2015 standards, 867 kg/m3 of density, 0.5 mg KOH/g of acid number, 1.52 cSt of kinematic viscosity, 48.081 MJ/kg of calorivic value and 143.99%- mass of methyl ester content.